Kebijakan Dividen Memoderasi Determinan yang Mempengaruhi Return Saham di Negara Asean-5 - Lusmeida, Herlina; Citra, Ondo (Jurnal Kajian Akuntansi, 2024)
This research aims to determine the influence of the level of profitability, investment decisions, funding decisions and dividend policy on stock returns and also to determine the ability of dividend policy to moderate the level of profitability, investment decisions and funding policies on stock returns in manufacturing sector companies listed on S&P Capital IQ in ASEAN-5 countries (Malaysia, Indonesia, Philippines, Thailand and Singapore). This research is a quantitative research, using a purposive sampling method, 126 samples were obtained during the 8 year research period (from 2014 to 2021), so there were 1,008 observations. The research results show that dividend policy and profitability have a positive effect on stock returns, but investment and funding decisions have a negative effect. Dividend policy strengthens the positive influence of profitability levels on stock returns, but dividend policy does not strengthen the positive influence of investment decisions and funding decisions on stock returns. The practical implication of this research is that companies must strive to increase the level of profitability and carefully consider the company's dividend policy because these two things will support the company's stock returns. The theoretical implication is that this research supports the signaling theory that the level of profitability and dividend policy is information that provides signals on stock returns.